METHODOLOGICAL ROLE OF THE REGISTER OF LAND RIGHTS (PANGEEA, 2025)
The most important right over the land is the property. But the right to property may be limited by legal restrictions and may be subject to responsibilities. So, the need for protection spreads not only on: interests, restrictions, responsibilities, bonds, etc. The object of registration and protection becomes wider from a social, economic, ecological point of view. The registration process belongs to the particularities of the evolution (development) of land law within the development of land relations, of the land reform carried out. In order to create rational conditions in the use of land resources in the Republic of Moldova, essential changes are needed in the content of rights over land, the development of forms of labor organization, respectively their protection.
Keywords: Register of rights; registration of rights; registration process; protection of law; cadastral registration